Some Economic Aspects of Sugar as a Strategic Commodity in Egypt - Shehata, Gaber Ahmed Bassyouni; Srour, Ahmed Hassan Ismaiel; Oraby, Shmoaa Awad Mohamed Soliman; El-Wakeel , Sahar El-Sayed El-Sayed; Zahran, Hanan Abd-Elmoneim (Advances in Social Sciences Research Journal, 2023)
The research aims mainly to study Egyptian food security of sugar through studying of several sub-objectives represented in: estimating some economic indicators of sugar in Egypt during the period (2008- 2020), studying of the most important indicators of food security of sugar, estimating the size of the food gap of sugar and knowledge of the most important factors responsible for, and studying the policies and means to achieve food security of sugar in Egypt. Descriptive and quantitative analysis were used. The study depends on secondary data, which collected from local and foreign sources during the period (2008- 2020). The conduct study shows that the most important variables specific to the food gap of sugar are all from the local production of sugar and domestic consumption of sugar where it was found that the impact of each of these two variables on sugar gap be negative. The study showed that the strategic stock of sugar is estimated at 1.15 million tons and the average national consumption of sugar is estimated at 2.17 million tons during the study period (2008-2020) with an annual average during that period , therefore, coefficient of sugar food security estimated at about 0.37, therefore it requires to take various actions that would lead to increase the size of the sugar strategic stock to enough half of it needs for domestic consumption even come close to the value of coefficient of food security, from suitable coefficient of sugar food security. The study showed that the policies and means to achieve sugar food security include horizontal agricultural development policy, vertical agricultural development policy, the policy of rationalizing the consumption of sugar, policy of consumer subsidy of sugar, and the policy of diversifying sources of imported sugar. In the light of the results of the study illustrated by research it has been possible to reach some of the following recommendations: 1- It is necessary to intensify efforts to agricultural extension and agricultural research centers in collaboration with factories engineers and agriculture departments and supervisors agricultural awareness of the importance of agriculture resistance to pests and diseases that affect the crop, and help them get on pesticides is harmful to the environment to do so. 2- Increasing of sugar production through the expansion of sugar crops, particularly sugar beet to the lack of water needs compared to sugar cane harvest in the new land. 3- Increasing of sugar productivity crops through dissemination of sugar varieties of high productivity and to suit every center of administrative centers in Egypt. 4- Rationalizing the consumption of sugar during dismiss the size of the loss of sugar. 5- to achieve food security has to be the need to develop awareness programs for the application of planning policy breeds where it is one of the most important determinants of the demand for i Egyptian imports of sugar. 6- it is important to put a national strategy to increase the self-sufficiency ratio of sugar with the need to import and distribute the amounts of diversification between different sources in order to avoid what might happen from political pressure in favor of the Egyptian economy is in the case of international political conditions change. 7- It is necessary to study the reduction commitments of support granted to the production and export in the sugar-exporting countries in order to reduce the negative effects on the Egyptian Saving.